An Investigation of Metaphors on the Concept of Teacher among Preservice Turkish Teachers - Aytan, Talat (EXPERT PROJECTS PUBLISHING, 2014)
The purpose of this study is to investigate the perception of preservice Turkish teachers with respect to the concept of teacher through metaphors. The research has the research pattern adopted the phenonienology pattern, a qualitative research approach which prioritizes examining and understanding social phenomena within the context they belong to. The participants consist of freshman students studying at the departments of Turkish Language Teaching at Yildiz Technical University (46), Sabahattin Zaim University (36) and Aydin University (32) during 2013-2014 academic year. The present study is of a particular importance since the sample includes preservice students from private universities. The questions pursued in the study are which metaphors preservice Turkish teachers produce for the concept of teacher and which conceptual categories those metaphors are sorted out based on their common features. To that end, the participants are asked to complete the sentence A teacher is like ..... , because ..... Content analysis, a qualitative data analysis method, is employed during the data analysis process. According to the findings, the preservice Turkish teachers have produced 42 valid metaphors. The results obtained in the research yield that preservice Turkish teachers consider the concept of teacher as source of information, mentor and guide, example of love and sacrifice, molder.
Keywords: preservice Turkish teachers; concept of teacher; metaphors; education; student; teacher; THINKING; Social Sciences - Other Topics